Effect of fluvalinate on the expression profile of circular RNA in brain tissue of Apis mellifera ligustica workers - Xueqing, Shan; Delong, Lou; Guizhi, Wang; Yunhan, Fan; Liuxu, Yang; Tianle, Chao (Frontiers in Genetics, 2023)
Fluvalinate is widely used in apiculture as an acaricide for removing Varroa mites, but there have been growing concerns about the negative effects of fluvalinate on honeybees in recent years. Previous research revealed changes in the miRNA and mRNA expression profiles of Apis mellifera ligustica brain tissues during fluvalinate exposure, as well as key genes and pathways. The role of circRNAs in this process, however, is unknown. The goal of this study was to discover the fluvalinate-induced changes in circular RNA (circRNA) expression profiles of brain tissue of A. mellifera ligustica workers. A total of 10,780 circRNAs were detected in A. mellifera ligustica brain tissue, of which eight were differentially expressed between at least two of the four time periods before and after fluvalinate administration, and six circRNAs were experimentally verified to be structurally correct, and their expression patterns were consistent with transcriptome sequencing results. Furthermore, ceRNA analysis revealed that five differentially expressed circRNAs (DECs) (novel_circ_012139, novel_circ_011690, novel_circ_002628, novel_circ_004765, and novel_circ_010008) were primarily involved in apoptosis-related functions by competitive binding with miRNAs. This study discovered changes in the circRNA expression profile of A. mellifera ligustica brain tissue caused by fluvalinate exposure, and it provides a useful reference for the biological function study of circRNAs in A. mellifera ligustica.